2005
DOI: 10.1038/sj.ijo.0803000
|View full text |Cite
|
Sign up to set email alerts
|

CRP reduction following gastric bypass surgery is most pronounced in insulin-sensitive subjects

Abstract: OBJECTIVE: Obesity is frequently associated with insulin resistance, dyslipidemia, hypertension and an increased risk of cardiovascular disease, reflected in elevated markers of inflammation, in particular C-reactive protein (CRP). To what extent the insulin resistance or the obesity per se contributes to increased CRP levels is unclear. In morbidly obese patients, gastric bypass surgery causes marked changes in body weight and improves metabolism, thereby providing informative material for studies on the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 48 publications
11
59
1
2
Order By: Relevance
“…Our investigation corroborates preliminary studies (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) as it shows that obesity is a state of chronic low-grade inflammation and the weight reduction resulting from bariatric surgery significantly improves the inflammatory state. This amelioration relies on the continuous reduction in hs-CRP and IL-6 concentrations, associated with a parallel decrease in BMI.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our investigation corroborates preliminary studies (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) as it shows that obesity is a state of chronic low-grade inflammation and the weight reduction resulting from bariatric surgery significantly improves the inflammatory state. This amelioration relies on the continuous reduction in hs-CRP and IL-6 concentrations, associated with a parallel decrease in BMI.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have demonstrated that surgically induced weight loss is accompanied by an improvement of the endothelial function (18,19,21) and the proinflammatory state (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, few studies have studied endothelial function and proinflammatory state together, and have considered different time-points to determine postsurgical changes.…”
Section: Introductionmentioning
confidence: 99%
“…One prospective study was excluded for the same reason, and four others were excluded for the unsuccessful weight loss intervention, which was defined as no significant difference (P [ 0.05) in BMI levels before and after intervention. The final meta-analysis was carried out with the remaining 11 cross-sectional studies [12][13][14][15][16][17][18][19][20][21][22] and 10 prospective studies with successful interventions through gastric surgery [23][24][25][26][27] or diet and exercise [17,[28][29][30][31] as only these met the respective inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it appears that heterogeneity of the studies may be due to a combination of other unknown factors and not simply a single one. Ten prospective studies comprising 353 participants who underwent weight loss by gastric surgery [23][24][25][26][27], or diet and/or exercise [17,[28][29][30][31] showed a significant decrease in SAA levels with weight loss represented by the pooled standardized mean difference of -0.480 (-0.678 to -0.283, P \ 0.0005) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…[73][74][75][76][77] Multiple regression analysis reveals that the decrease in postoperative insulin resistance after surgery is independently associated with a decrease in interleukin-6 concentrations. 77 At 6 months after surgery, there is also an increase in the production of interferongamma, IL-12, and IL-18 that is associated with a rise in natural killer (NK) cell activity.…”
Section: Anti-inflammatory and Immune Effectsmentioning
confidence: 99%